Earthdivers (2022), volume 2 ebook Ice age. - Jones, Stephen Graham (Earthdivers (2022), 2024)
Guest artists Riccardo Burchielli (DMZ), Patricio Delpeche, and Emily Schnall join Stephen Graham Jones—New York Times best-selling author of The Only Good Indians and My Heart Is a Chainsaw—for a mission to the Ice Age exploring America's pre-Columbian past! When Martin and Tawny's children disappeared, the couple barreled into the desert to track them down at any cost. Instead, they ran afoul of another group of rovers who claimed to be saving the world by traveling through a cave portal to the year 1492 to prevent the creation of America—an idea that defied belief until the grieving parents were lured into the cave and vanished in time and space. Now alone, Tawny must adapt to the wild marshlands of prehistoric Florida, circa 20,000 BC, and the breathtaking and bloodthirsty megafauna are the least of her problems when she's caught in a war between a community of native Paleo-Indians and an occupying Solutrean force. Tawny's odds of survival are in free fall, but she's a mother on a mission…and she's holding on to hope that the cave brought her here for a family reunion. In the tradition of Saga, the next chapter of the critically acclaimed sci-fi epic is here in Earthdivers Vol. 2. Collects Earthdivers #7-10.